Toric Intraocular Lenses for the Management of Corneal Astigmatism at the Time of Cataract Surgery - Colm McAlinden; David Janicek (Journal of Ophthalmology, 2021)
Aims/Background. To assess astigmatic outcomes with the use of toric intraocular lenses (IOLs) for patients with significant amounts of corneal astigmatism undergoing cataract surgery. Methods. This audit was conducted in a UK ophthalmology department and included 48 eyes of 42 patients. Surgery was performed during 2019 in patients with 2.50 diopters (D) or more corneal astigmatism. Anterior keratometry readings were used to determine the toric IOL power. Vector analysis using the Alpins method was used to assess changes in astigmatism pre to postoperatively. Results. There were 18 right and 26 left eyes included. In terms of gender, 61% of patients were female and 39% were male. The mean (±standard deviation (SD)) age was 70 (±11) years. The mean (±SD) axial length, K1, K2, and delta K was 23.55 (±1.4) mm, 42.71 (±1.39) D, 45.78 (±1.60) D, and 3.01 (±0.89) D, respectively. Postoperatively, the median spherical, cylinder, and spherical equivalent refraction was 0.00 D, −1.00 D, and 0.00 D, respectively. Postoperatively, 41% of the eyes had ≤0.50 D of spectacle astigmatism and 80% had ≤1.00 D. No patient required a secondary procedure to reposition the IOL from rotation. In vector analysis with the use of polar diagrams, there was a tendency for overcorrection of with-the-rule astigmatism and undercorrection of against-the-rule astigmatism. Conclusions. Significant reductions in astigmatism can be achieved with the use of toric IOLs in patients undergoing cataract surgery. Further improvements may be possible with surgeon-specific determination of their surgically induced astigmatism and flattening effect from the main corneal incision. Furthermore, the use of an optical biometer that directly measures the posterior corneal curvature and permits automatic toric IOL power determination with modern formulas avoiding the need for manual data entry may reduce the risk of human error and improve visual and refractive outcomes.